The income concentration among the rich in Brazil, 2012-2019 - Breviglieri, Tatiana Figueiredo [UNESP]; Correa, André Luiz [UNESP] (FapUNIFESP (SciELO), 2023)
The main objective of the paper is to analyze the trajectory and level of inequality in Brazil between 2012 and 2019 by calculating the concentration of Brazilian income at the top of the distribution pyramid using tax data obtained by the Receita Federal do Brasil (Brazil’s Federal Tax Office). In addition to the richest 1%, the study also identified other even more concentrated strata, 0.1% and 0.05%. The methodology adopted was Pareto Interpolation, which made it possible to obtain the proportion of national income held at the top of the pyramid. The hypothesis is that inequality seen from the top is high and there is no indication of a decline even in the face of the economic crisis from 2014 onwards. The results obtained corroborate this hypothesis: the calculations indicate that the percentage of income held by the richest 1% fluctuated little around 22%.
A concentração da renda entre os ricos no Brasil, 2012-2019
Keywords: income concentration; inequality; taxation